Visualizing Spatial Evolution of Electron-Correlated Interface in Two-Dimensional Heterostructures - Zhang, Quanzhen; Hou, Yanhui; Zhang, Teng; Xu, Ziqiang; Huang, Zeping; Yuan, Peiwen; Jia, Liangguang; Yang, Huixia; Huang, Yuan; Ji, Wei; Qiao, Jingsi; Wu, Xu; et al. (ACS nano, 2021)
Microscopically visualizing the evolution of electronic structures at the interface between two electron-correlated domains shows fundamental importance in both material science and physics. Here, we report scanning tunneling microscopy and spectroscopy studies of the interfacial electronic structures evolution in a phase-engineered monolayer NbSe2 heterostructure. The H-NbSe2 metallic state penetrates the Mott insulating T-NbSe2 at the H/T phase interface, with a prominent 2D charge density wave (CDW) proximity effect. Moreover, an insulating Mott gap collapse with the disappearance of the upper Hubbard band is detected at the electronic phase transition region. Theoretical calculations reveal that such insulating Mott gap collapse can be attributed to the electron doping effect induced by the interface. Our findings promote a microscopical understanding of the interactions between different electron-correlated systems and provide an effective method for controlling the Mott insulating states with phase engineering.